Aligning Information Literacy Assessment with Metacognitive Strategies - Hostetler, Kirsten; Luo, Tian; Stefaniak, Jill (Journal of University Teaching and Learning Practice, 2018)
Despite the popularity of metacognitive research, and the inclusion of similar concepts in professional guidelines, librarians have not incorporated metacognitive tools into their assessment strategies. This systematic literature review found (1) metacognitive assessments can act as a learning aide in encouraging higher-order thinking; (2) metacognitive assessments can be effective measurements under proper conditions with experienced learners; and (3) librarians have limited options when selecting assessment tools even as the demand for demonstrating the library’s value to stakeholders is increasing. The paper concludes with gaps in the literature and areas for future directions.